Accuracy of dental implant placement using static versus dynamic computer-assisted implant surgery: An in vitro study. (May 2023) - Taheri Otaghsara, Seyedeh Sahar; Joda, Tim; Thieringer, Florian Markus
Abstract: Objectives: This in-vitro study compared the accuracy of implant placement using static versus dynamic computer-assisted implant surgery (CAIS) at two implant sites. Methods: Partially edentulous maxillary models were 3D-printed, and two implants (Straumann TL RN 4.1 × 10 mm) were inserted in FDI positions 15 and 16 per model using two CAIS approaches (10 models per approach). A three-dimensional (3D) reconstruction tool was used for implant planning, surgical guide design, and measuring implant positioning accuracy. In static CAIS, the implants were placed with 3D-printed surgical guides ( n  = 20); in dynamic CAIS, real-time navigation was performed ( n  = 20). Primary outcomes were defined as coronal and apical global deviation as well as angular deviations and deviation comparison between implants placed at positions 15 and 16; the secondary outcome was the bi-directional deviation in mesial-distal, buccal-palatal, and apical-coronal direction. Results: The mean coronal and apical global deviation for static CAIS for implant positions 15 were 0.88±0.31 mm and 1.45±0.37 mm, and for implant position 16 were 0.67±0.31 mm, and 1.07±0.32 mm, respectively. In dynamic CAIS, the mean coronal and apical global deviation for implant position 15 were 0.97±0.32 mm and 1.58±0.56 mm, and for implant position 16 were 0.79±0.29 mm and 1 ± 0.37 mm, respectively. Buccal-palatal deviation was higher using static CAIS, and mesial-distal deviation was higher in dynamic CAIS. In position 15, mesial-distal deviation at the apex and the platform were lower in static approaches than in dynamic ones. In implant position 16, buccal-palatal deviation at the apex was lower in the dynamic group than with static ones. For bi-directional analysis, buccal-palatal deviation at the platform ( P  = 0.0028) and mesial-distal deviation at the apex ( P  = 0.0056) were significantly lower in molar sites using static CAIS. Mesial-distal deviation at the apex ( P  = 0.0246) revealed significantly lower values in position 16 following dynamic CAIS. Conclusions: Both static and dynamic CAIS resulted in accurate implant placement. However, dynamic CAIS exhibited higher deviation in the mesial direction in an in-vitro setting. In addition, the implant site affects the accuracy of both CAIS approaches. Clinical significance: Both static and dynamic CAIS demonstrate high accuracy for guided implant placement..